PENGARUH LATIHAN SINGLE LEG SPEED HOP TERHADAP POWER OTOT TUNGKAI MAHASISWI KELAS A ANGKATAN 2014 PENDIDIKAN KEPELATIHAN OLAHRAGA UNIVERSITAS RIAU - Eko Rizaldi; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is based on the statement submitted to the lecturers who have authority during the lecture activities, student IVA Education Sports coaching is still said to be weak in the power aspect. This is evidenced by the number of female students who are unable to achieve the standard that has been determined by the lecturer. In addition, it is also seen when rejecting female students look slow so that the jump results short. This research was conducted to find out whether there is Influence of Single Leg Speed Hop Exercise Against Muscular Power of Student Limbs IVa Education of Sports Coaching University of Riau. The sample in this research is HUHA Junior Putra Volleyball team Pekanbaru and amounted to 6 people. The sampling technique is the whole population (total sampling). Instrument performed in this research is standing arm jump test, which aims to measure leg muscle power. After that, the data were processed with statistics, to test the normality by lilifors test at a significant level of 0.05α. The hypothesis proposed is that there is influence of Single Leg Speed Hop Exercise Against Muscular Power of Student's limbs IVa Education of Sports Coaching University of Riau. Based on lilifors test analysis yield Lhitung (Preetest) equal to 0,1515 and Ltabel 0,319, Lhitung (Posttest) equal to 0,2061 and Ltabel 0,319 mean Lhitung <Ltabel, hence sample come from normal berkristribusi population. Then from calculation result of t test analysis yield t count equal to 6,16 and ttable 2,015. Means thitung> ttabel. It can be concluded that H0 is rejected H1 accepted. Thus there is Influence Single Leg Speed Hop Exercise Against Muscle Power Student Legs IVa Education Sports Coaching University of RiauKeywords: single leg speed hop, explosive power of leg muscles